PENGARUH MOTIVASI BERPRESTASI TERHADAP HASIL BELAJAR SISWA KELAS X DI SMAN 06 PONTIANAK TIMUR - Ramadan, Rizky; Herkulana, Herkulana; Genjik, Bambang (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
Â AbstractThe title of this reasearch â€œ"The Effect of Achievement Motivation on Student Learning Outcomes at SMAN 06 East Pontianak". Learning outcomes have a very important position in achieving learning objectives. Achievement of learning outcomes can not be separated from the learning process of students. Student learning outcomes are high, showing success in learning and learning activities. Conversely, if the results achieved are low, the learning objectives have not been achieved. The results of research that researchers have done, namely in the process of teaching and learning activities showed 58.25% of respondents stated very good, 37.86% of respondents said good, 2.91% of respondents said it was good enough, and 0.97% said it was not good. It can be interpreted that the achievement motivation in SMAN 06 Pontianak is included in the very good category. Based on research conducted by researchers that the equation Y = 10,418 + 1,247X, this means that every increase in achievement motivation (X) is 1 (one), the learning outcomes (Y) will increase by 1,247. Because tcount> ttable (18,035> 1,983) Ha is accepted and Ho is rejected or "There is an influence of achievement motivation on student learning outcomes at SMA Negeri 6 Pontianak".keywords: learning outcomes, learning motivation, economic subjects